Valorisation of Sarawak Liberica coffee cascara and spent grounds: GC-MS profiling and prototype development of tea and soap - Bryan Voon, Li Qi; Elexson, Nillian; TUNJUNG, MAHATMANTO; Wendy Bekti, Sunarharum; Yuniar Ponco, Prananto (Department of Food Science and Technology, Universitas Hasanuddin, 2026)
Coffee processing generates substantial by-products such as cascara and spent coffee grounds, which remain underutilised despite their potential for value-added applications. This study aimed to evaluate the utilisation of Sarawak Liberica coffee byproducts through the development of cascara tea and soap prototypes. Bioactive compounds in the ethanolic extract of cascara powder were identified using gas chromatography–mass spectrometry (GC-MS). Cascara powder was formulated into original and flavoured tea variants and evaluated using a 9-point hedonic scale. Soap prototypes incorporating cascara and spent coffee grounds were produced via the cold process method and assessed for total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity using standard colorimetric assays. The flavoured cascara tea demonstrated higher sensory acceptance across multiple attributes compared to the original formulation. GC-MS analysis identified 30 bioactive compounds, indicating functional potential. Both cascara-based soaps and spent coffee ground-based soaps exhibited TPC and TFC value with strong antioxidant activity, with optimal performance observed at higher incorporation levels. Collectively, these findings highlight the feasibility of transforming Sarawak Liberica coffee by-products into value-added functional food and cosmetic products, providing a sustainable approach to waste utilisation while expanding their industrial application potential.